Efeito vasodilatador de fragmentos angiotensinérgicos no leito coronariano de ratos - Patricia Lanza de Moraes (2013)
The renin-angiotensin system is a hormonal system composed by several enzymes, peptides and receptors. Angiotensin(Ang)-(1-7) is one of the recently described peptides of this system, which holds biological activity. The aim of this study was to evaluate the vasodilatory effect of Ang-(1-7) in coronary bed of rats, as well as to investigate biological activities of small peptides that can be derived from Ang-(1-7). Hearts of Wistar rats were perfused according to the Langendorff technique (constant flow) with Krebs-Ringer solution (KRS) or KRS containing Ang-(1-7). Ang II was utilized as a positive control. Ang-(1-7) presented a vasodilatory effect in coronary bed of rats (-20.15 ± 5.14 mmHg), which involved the participation of Mas, angiotensin-converting enzyme (ACE) and ACE2. Furthermore, Ang-(1-7) reduced the cardiac activity. The participation of ACE and ACE2 in the Ang-(1-7) effects suggested that the formation of small peptides might be involved in these effects. Thus, we evaluated the actions of Ang-(1-5), Ang-(1-4), Ang-(1-3) and Ang-(1-2) (42 pM) in isolated hearts. Ang-(1-4), Ang-(1-3) and Ang-(1-2) induced a reduction in the perfusion pressure, indicating vasodilation. Because Ang-(1-2) is the smallest peptide tested and presented the major effect, we decided to investigate its mechanisms of action. A-779, a Mas antagonist, partially blunted the Ang-(1-2) effects, as well as captopril, an ACE inhibitor, while L-NAME completely inhibited its vasodilatory effect. L-arginine was tested in the same experimental conditions to exam whether the Ang-(1-2) effects were due to the presence of arginine in its composition. We found that L-arginine did not cause any significant effect in the coronary bed. In order to investigate if Ang-(1-2) is also able to produce changes in blood pressure, awake Wistar and spontaneously hypertensive rats (SHR) were submitted to intravenous injection of Ang-(1-2) at 20 nM. In SHR, but not in Wistar rats, Ang-(1-2) was capable to produce a significant reduction in the mean arterial pressure without changes in heart rate. Our results indicate that Ang-(1-7) is able to induce a direct vasodilatory effect in coronary bed of rats by a mechanism involving Mas, ACE and ACE2. Also, small peptides [Ang-(1-4), Ang-(1-3) and Ang-(1-2)] likely formed due to ACE and ACE2 actions participated of this effect. Furthermore, Ang-(1-2) reduced the arterial pressure of awake SHR.